Home mechanical ventilation: outcomes according to remoteness from health center and different family education levels - Pekcan, Sevgi; Aslan, Ayşe Tana; Kiper, Nural; Köse, Mehmet; Cobanoglu, Nazan; Yalçin, Ebru; Doğru, Deniz; Ozçelik, Uğur (The Turkish Journal of Pediatrics, 2010)
Throughout the world, home mechanical ventilation (HMV) is being increasingly employed to treat patients suffering from chronic respiratory failure. This present study aimed to examine the characteristics and outcomes of 27 children seen in our department over a four-year period who were treated with HMV. The causes of chronic respiratory failure were as follows: 16 (59.3%) neuromuscular disease, 6 (22.2%) primary respiratory diseases, 3 (11.1%) congenital heart disease, and 2 (7.4%) storage disease. The mean age was 59.4 months (1 day-15 years); mean follow-up for invasive ventilation was 356 (0-1200) days and for non-invasive HMV was 517 (30-1440) days. With respect to maternal educational level, 13 had graduated from elementary school and 14 from high school or university. Nine of our patients resided in Ankara, while 18 lived in rural areas of Turkey. Eleven of the 27 patients died during the HMV period (1-36 months) at home. Five patients were weaned from HMV between 1-19 months. Our experience showed that HMV can be applied successfully in chronic respiratory failure patients in Turkey. Length of the follow-up period and mortality rate were not affected by the patient’s place of residence (city center or rural) or maternal level of education.